Impactos socioambientais da terapia assistida com o Boto-cor-de-rosa (inia geoffrensis) no município de Iranduba – Am - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The bototerapia is a therapy technique assisted by animals in the case by the Amazon River Dolphin (Inia geoffrensis). This activity was developed in Amazons, from 2005, by the physiotherapist Igor Simões Andrade, inspired by other therapies on animals, specifically delfinoterapia involving dolphin saltwater. The bototerapia has its foundations in the physical principles of water (buoyancy, hydrostatic pressure, buoyancy, etc.) added to the playful context that brings the presence of the button for the treatment of disorders such as autism, Down syndrome and cerebral palsy. This study is justified by the scarcity of scientific studies on the relationship between humans and porpoises-color pink and the bototerapia, being a pioneer in this sense, this study may participate in the improvement of knowledge in this regard. It is a descriptive and analytical work of qualitative that aimed to analyze the environmental impacts of bototerapia discussing its benefits and risks in terms of health (zoonoses, injury risk to patients or the therapist), analyzing their contribution to the conservation of the species, questioning the ethical and legal aspects of regulation of this practice, and comparing with other activities involving small cetaceans (delfinoterapia, dolphin interaction with tourism). For this, they were mobilized different search tools: documentary and bibliographical research, field observations and semi-structured interviews with three categories of actors (social, therapy and conservation). The category of social actors represented by fishermen, was an interview in São Thome community in the municipality of Iranduba - AM adjacent to the floating of David where bototerapia is performed. After literature review and data analysis, we came to the conclusion that bototerapia brings different problems as their economic sustainability and may contribute to increased conflicts with fishermen taking into account the content analysis of the interviews obtained in the region, and potentially be able to let humans and animals involved in vulnerable bototrepaia zoonoses and injuries while running. On the other hand, it seems to meet its objectives in therapeutic terms, and has the potential for animal conservation can change the shape of human realize the button. Compared to other activities involving small cetaceans to bototerapia has a smaller impact on the behavior of animals involved and their living conditions, in addition, using the criteria of animal ethics of Martha Nussbaum it was less problematic from a moral point of view.
Keywords: Bototerapia; Boto cor-de-rosa; CIENCIAS BIOLOGICAS